PELAKSANAAN KOMUNIKASI INFORMASI EDUKASI (KIE) KB MKJP DI KABUPATEN SIJUNJUNG - Welda Yulia; Ernita Arif (Jurnal Kependudukan dan Pembangunan Lingkungan, 2021)
BKKBN has a duty as an institution that carries out efforts to control population quantity and organizes Family Planning (KB) through the implementation of advocacy and KIE. This means that KIE is a powerful weapon in the achievement of the Bangga Kencana program. Especially in an effort to reduce the Total Fertility Rate (TFR) and Population Growth Rate (LPP). TFR and LPP will decrease if Fertile Age Couples (PUS) use the Long-Term Contraception Method (MKJP) because MKJP is considered a Rational, Effective and Efficient (REE) contraception. Therefore, the achievement of MKJP is a concern and priority in the Bangga Kencana program. The maximum implementation of KIE will result in satisfactory results. The purpose of this study was to determine the achievement of the KB MKJP in 2020, the KIE media used and the types of KIE activities in Sijunjung Regency. The research method used is descriptive qualitative, the informants are KB extension, cadres, PUS, Kasi advocacy and mobilization. Data collection techniques through in-depth interviews and documentation, processing primary and secondary data through data reduction techniques, presentation and drawing conclusions. The results of the research show that the implementation of KIE KB MKJP in Sijunjung Regency has not been maximally carried out. PKB, PLKB and Bangga Kencana program managers have conducted KIE using media such as leaflets, booklets, posters, ABPK, flipcharts, billboards, banners, videos, social media and using the Information Unit Car (MUPEN). The types of KIE activities carried out are mass, group, individual KIE using the communication network that has been established in the field.